Prediction Performance Comparison of Risk Management and Control Mode in Regional Sites Based on Decision Tree and Neural Network - Zhu, Wenhui; He, Jun; Zhang, Hongzhen; Cheng, Liang; Yang, Xintong; Wang, Xiahui; Ji, Guohua (Frontiers in Public Health, 2022)
The traditional risk management and control mode (RMCM) in regional sites has the defects of low efficiency, high cost and lack of systematicness. Trying to resolve these defects and explore the application possibility of Machine Learning, characteristic data set for RMCM in regional sites was established. Three decision tree (DT) algorithms (CHAID, EXHAUSTIVE CHAID and CART) and two artificial neural network (ANN) algorithms (BP and RBF) were implemented to predict RMCM in regional sites. The results showed that in the aspects of accuracy (ACC), precision (PRE), recall ratio (REC) and F1 value, CART-DT was superior to CHAID-DT and EXHAUSTIVE CHAID-DT (E-CHAID-DT), and BP-ANN was superior to RBF-ANN. However, CART-DT was inferior to BP-ANN in ACC, PRE, REC and F1 value. BP-ANN model is good at nonlinear mapping, and it has flexible network structure, and low risk of over fitting. The case study of a typical county demonstration area confirmed the extensibility of the method, and the method has great potential in RMCM prediction in regional sites in the future.